2009
DOI: 10.1021/jf901786p
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Anticholinesterase and Antimicrobial Activities of Supercritical versus Conventional Extracts of Satureja montana

Abstract: Winter savory Satureja montana is a medicinal herb used in traditional gastronomy for seasoning meats and salads. This study reports a comparison between conventional (hydrodistillation, HD, and Soxhlet extraction, SE) and alternative (supercritical fluid extraction, SFE) extraction methods to assess the best option to obtain bioactive compounds. Two different types of extracts were tested, the volatile (SFE-90 bar, second separator vs HD) and the nonvolatile fractions (SFE-250 bar, first and second separator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 28 publications
2
39
0
2
Order By: Relevance
“…According to this report, it is concluded that the oil interferes with malathioninduced stimulation of hepatic cells glycogenolysis and gluconeogenesis through its antioxidant potential and increasing AChE activity. AChE inhibitory activity of the essential oil of S. montana was investigated by Silva et al (2009). According to this study, inhibitory activity over AChE by S. montana was assessed as a potential indicator for the control of Alzheimer's disease.…”
Section: Acetylcholinesterase (Ache) and Butyrylcholinesterase (Bche)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to this report, it is concluded that the oil interferes with malathioninduced stimulation of hepatic cells glycogenolysis and gluconeogenesis through its antioxidant potential and increasing AChE activity. AChE inhibitory activity of the essential oil of S. montana was investigated by Silva et al (2009). According to this study, inhibitory activity over AChE by S. montana was assessed as a potential indicator for the control of Alzheimer's disease.…”
Section: Acetylcholinesterase (Ache) and Butyrylcholinesterase (Bche)mentioning
confidence: 99%
“…Flavan-3-ols (catechin and epicatechin) (Cetkovic et al, 2007b;Cetojevic-Simin et al, 2012;Palavra et al, 2011;Silva et al, 2009) and flavanonols (aromadendrin, taxifolin) (Malmir et al, 2012; are other flavonoid aglycones found in Satureja species (Table 5).…”
Section: Flavonoids and Related Compoundsmentioning
confidence: 99%
“…The strongest antibacterial activity was found against B. cereus and B. subtilis. Carvacrol (91, Figure 21), p-cymene (63, Figure 14), thymol (73, Figure 16), and γ-terpinene (53, Figure 11) were the major compounds detected in SFE volatile extracts [139].…”
Section: Antibacterial and Cytotoxic Activitymentioning
confidence: 99%
“…Satureja montana é comumente conhecida como segurelha de inverno ou segurelha montanhesa é forte erva aromática e tem sido usada a centenas de anos como condimento de alimentos e chás, utilizada na comida mediterrânea, principalmente como tempero de carnes e peixes (Prieto et al, 2007;Silva et al, 2009). Na medicina tradicional e homeopática a segurelha de inverno é utilizada em várias enfermidades, principalmente digestiva, como cólica e diarréia; estimulantes, espectorantes, carminativos, anticatarraise afrodisíaco (Ćetkovićet al, 2007;Oliveira et al, 2011).…”
Section: Introductionunclassified